Multi-scale drivers of riparian vegetation form and function in ephemeral stream networks of the Sonoran Desert - Shaw, Jeremy Robert, author; Cooper, David J., advisor; Merritt, David M., committee member; Ramirez, Jorge A., committee member; Ryan, Michael G., committee member; Wohl, Ellen E., committee member (Colorado State University. Libraries, 2015)
To identify the drivers of riparian vegetation form and function throughout ephemeral watersheds of the Sonoran Desert, I investigated factors that condition plant responses to hydrologic fluxes across spatial scales ranging from watersheds to shrub canopies. Community composition and tree water relations were examined within the framework of a hydrogeomorphic stream classification defined by channel planform, boundary materials, and lateral confinement. The cover and density of perennial plant species and functional groups differed among stream types. Compositional differences between stream classes corresponded to variation in channel gradient, highlighting the role of fluvial disturbance in structuring riparian plant communities. Seasonal patterns of water stress and subsurface water sources for the four most abundant tree species also differed among stream types. Water stress was most severe and persistent in headwater streams, where thin alluvium limited water storage. Periodic flood recharge was stored in deep alluvium (>1 m) along downstream channel segments, reducing seasonal water stress for extended periods. In these stream types, riparian trees relied on shallow water sources (<50 cm) throughout much of the year, but accessed deeper water sources during summer droughts. Subsurface water sources were more variable in headwater stream types. Ecohydrological processes in these arid stream networks were driven by rainfall and streamflow pulses, but mediated by alluvial characteristics. I also conducted a two-year factorial field experiment to understand the factors limiting riparian tree establishment, and clarify how facilitative mechanisms vary with annual rainfall. Seedling survival was most strongly dependent on herbivore protection provided by nurse shrubs, regardless of precipitation amounts. In contrast, the importance of facilitation through canopy shading varied with increasing annual rainfall. Despite strong effects on survival, seedling growth rates were insensitive to annual rainfall.
Keywords: ecohydrology; ephemeral stream; facilitation; plant water sources; riparian vegetation